"Rape Is a Four-Letter Word": Psychosis, Sexual Assault, and Abortion in the 2012 U.S. Election. Issue 3 (2nd July 2020) - Stone Watt, Sarah
Abstract: Republican candidates made headlines during the 2012 election season for their offensive statements regarding rape when defending a comprehensive ban on abortion. Using Lacan's theory of psychosis, this article exposes unconscious rhetorical structures that may have contributed to the repetition of those gaffes even after the Republican Party advised all candidates to stop talking about rape. I argue that the repetition of controversial comments, during and after candidates' attempts to retract their inaccurate statements, was the result of a foreclosure in the minds of some candidates. The discursive structure of their comments provides evidence that some candidates were unable to reconcile White patriarchal subjectivity with the inability to protect against rape.